Neural mechanisms of different types of envy: a meta-analysis of activation likelihood estimation methods for brain imaging - Dai, Shuchang; Liu, Qing; Chai, Hao; Zhang, Wenjuan (Frontiers in Psychology, 2024)
Previous studies have a lack of meta-analytic studies comparing the trait (personality) envy, social comparison envy, and love-envy, and the understanding of the similarities and differences in the neural mechanisms behind them is relatively unclear. A meta-analysis of activation likelihood estimates was conducted using 13 functional magnetic resonance imaging studies. Studies first used single meta-analyses to identify brain activation areas for the three envy types. Further, joint and comparative analyses were followed to assess the common and unique neural activities among the three envy types. A single meta-analysis showed that the critical brain regions activated by trait (personality) envy included the inferior frontal gyrus, cingulate gyrus, middle frontal gyrus, lentiform nucleus and so on.The critical brain regions activated by social comparison envy included the middle frontal gyrus, inferior frontal gyrus, medial frontal gyrus, precuneus and so on. The critical brain regions activated by love-envy included the inferior frontal gyrus, superior frontal gyrus, cingulate gyrus, insula and so on. In terms of the mechanisms that generate the three types of envy, each of them is unique when it comes to the perception of stimuli in a context; In terms of the emotion regulation mechanisms of envy, the three types of envy share very similar neural mechanisms. Both their generation and regulation mechanisms are largely consistent with the cognitive control model of emotion regulation. The results of the joint analysis showed that the brain areas co-activated by trait (personality) envy and social comparison envy were frontal sub-gyral, inferior parietal lobule, inferior frontal gyrus, precuneus and so on; the brain areas co-activated by trait (personality) envy and love-envy were extra-nuclear lobule, lentiform nucleus, paracentral lobule, cingulate gyrus and so on; the brain regions that are co-activated by social comparison envy and love-envy are anterior cingulate gyrus, insula, supramarginal gyrus, inferior frontal gyrus and so on. The results of the comparative analysis showed no activation clusters in the comparisons of the three types of envy.